The Use of E-Sabak in Mathematics Learning to Optimize Higher-Order Thinking Skills - Muhammad Fajri (Study Program of Education for Islamic Elementary School Teachers (Undergraduate), Faculty of Tarbiyah and Education (FITK), Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
This study aims to describe the using of e-sabak in optimizing the higher-order thinking skills in mathematics learning. The obtaining data on the description of mathematics learning through the use of e-sabak in optimizing higher-order thinking skills, this research applied a qualitative approach with a descriptive method. The research instrument utilized observation and documentation guidelines to photograph mathematics learning in optimizing the ability to think at a higher level through the use of e-sabak in fourth-grade students at SDN Pondok Petir 01, Depok City. The results showed: (1) students were happy with new experiences in the use of e-sabak; (2) the use of e-sabak devices can optimize the ability of students to analyze and evaluate phenomena through observation by capturing them using e-sabak; (3) teacher provided the ways of communicating observations in front of the class to students; (4) the ability of students to create a problem-solving context still needs to be optimized through the praxis of learning in the classroom context. This study concluded that the e-sabak device helps the implementation of mathematics teaching to maximize the ability of high-level thinking students in fourth grade SDN Pondok Petir 01, Depok City.